Regulatory Framework on Ocean Threats – Transportation Law Analysis to Multiple Oil-Spill Cases in Indonesia - Ariadi Subagyono, Bambang Sugeng; Maradona; Yunita Sabrie, Hilda; Romadhona, Mochamad Kevin; Suheryadi, Bambang; Chumaida, Zahry Vandawati; Anggraeni, Ajeng (Transactions on Maritime Science, 2024)
This research aims to analyse the legislation pertaining to the environment and transportation as outlined in Article 1 point 1 of Law No. 22 of 2001, which deals with oil and natural gas. The Minister of Energy and Mineral Resources' Regulation No. 7 of 2019 Article 1.2 relates to the management and use of oil and gas. Articles 316, 318-322, 324-329, and 332 govern criminal offenses committed in the maritime domain. This study employs a doctrinal legal research methodology, using both conceptual approach and statutory approach. The agreement for the maritime transportation of commodities establishes rights and duties that the involved parties are required to fulfill. One of the duties and liabilities of the carrier is to maintain the security of the vessel and the merchandise it transports. The legal framework governing the transportation of commodities is established under Articles 466 to 520 of the Criminal Code. This concept is founded upon two additional ideas, i.e. strict liability and the absence of the necessity to establish the party responsible for environmental damage prior to attributing blame. The principle of strict responsibility in Indonesian national law is governed by Article 88 of Law No. 32 of 2009, which pertains to environmental protection and management. This article only focuses on the environmental degradation and marine contamination resulting from oil spills. The obligation for transportation in maritime agreements and the legal repercussions for causing marine pollution must be followed by all the sea transportations company especially carrying dangerous material.